Molecular identification using DNA barcoding and pharmacognostical evaluation of Justicia beddomei (C. B. Clarke) Bennet - Nagalekshmi Rajeswariammal, Senthilkumar Palaniappan (Journal of Applied Pharmaceutical Science, 2024)
Justicia beddomei (C.B. Clarke) Bennet has been utilized for many years in the traditional medical system. This study aimed to facilitate the identification of J. beddomei (C.B. Clarke) Bennet using trnH–psbA DNA barcode region, NCBI database, and pharmacognostical features of the plant parts. Genomic DNA was extracted from plant leaf samples and polymerase chain reaction amplification and DNA sequence determination were performed. The contigs DNA sequence 319 bp was analyzed using the similarity basic search method BLASTn. The trnH– psbA barcode region of 319 bp contigs sequence showed 100% similarity with the standard sequence of J. beddomei with the Accession No. MK347214.1 from the NCBI database. Microscopical studies of the different parts of the plant facilitate the identification and differentiation of J. beddomei from its morphologically similar and confusing plant Justicia adhatoda L. Justicia beddomei can be easily identified by the flower and its inflorescence arrangement. The other identification features are the presence of cystoliths in the mesophyll region of the leaf, and the presence of colored content and crystals in the powder microscopic analysis. The outcome of the present detailed microscopic study of the stem, leaf, and flower of J. beddomei is of great value in the identification of the powdered samples and their adulterants.
Keywords: Justicia beddomei (C.B. Clarke) Bennet, trnH–psbA barcode, NCBI database, pharmacognostical studies, molecular identification, DNA sequence